Impact of glaucoma on vision-specific quality of life in monocular glaucoma patients using the Indian vision function questionnaire - Devendra Maheshwari; Isha Ingle; Techi Dodum Tara; Sarika Ramugade-Shinde; Madhavi R Pillai; Mohideen A Kader; Ramakrishnan Rengappa; Mohammed Sithiq Uduman (Indian Journal of Ophthalmology, 2023)
Purpose: To evaluate the determinants affecting the quality of life in monocular glaucoma patients using the Indian vision function questionnaire. Methods: In this prospective cross-sectional study, total of 196 patients were divided into two groups: cases and controls. Indian Vision Function Questionnaire (IND-VFQ) was administered and analyzed. One hundred twenty-nine (58.6%) patients who had lost their vision in one eye due to glaucoma were included as cases and 67 (30.4%) patients who had lost their vision due to other causes were taken as controls. Results: Median composite score of subscales was 54.62 (29.7–74.7) in group 1 and 45.38 (23.7–76.7) in group 2. The psychosocial impact scale was the most affected scale, the median scores were 33.02 (0 to 60.0) and 19.07 (0 to 53.0) in groups 1 and 2, respectively. Among all dimensions of IND-VFQ, the highest score was for color vision 100.0 (0–100.0) and 100.0 (0–100.0), and the lowest median score was found in mental health and dependency in both the groups. Multiple linear regression analysis demonstrated that visual acuity was associated with a low score (P < 0.001). Female gender was significantly associated with the overall score in the univariate model (P = 0.006). Conclusion: Monocular glaucoma patients have a poor general and vision-related quality of life. Depression associated with monocularity and the perception of dependency and being a burden on their family members greatly impacted the mental health of the participants.